1993
DOI: 10.1212/wnl.43.9.1789
|View full text |Cite
|
Sign up to set email alerts
|

Wada memory testing and hippocampal volume measurements in the evaluation for temporal lobectomy

Abstract: We examined the relationship of Wada memory performance and MRI hippocampal volume measurements to laterality of ultimate seizure localization in 20 patients with complex partial seizures who later underwent temporal lobectomy. Discriminant function analysis employing both Wada memory test asymmetries and hippocampal volume asymmetries correctly classified 100% of the patients into left and right temporal lobe groups. Wada memory asymmetries alone correctly classified 90% of the sample (80% of the sample when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 0 publications
6
58
1
Order By: Relevance
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
“…Initial studies focused exclusively on hippocampal volumes and their relationship to memory dysfunction in temporal lobe epilepsy (TLE) ((1-3), for a review, see (4)). These studies demonstrated a consistent relationship between reductions in left hippocampal volume, or hippocampal asymmetries, and impairments in verbal learning and memory, in TLE patients who were left-hemisphere dominant for language (1,2,(5)(6)(7)(8)(9). More importantly, these studies established that patients without left hippocampal volume loss were at greatest risk for postoperative memory decline (7).…”
Section: Imaging Of Structure and Metabolites In Epilepsy 21 Volumetmentioning
confidence: 66%
“…Furthermore, the presence of HS is known to be associated with an earlier age at onset of epilepsy (14,20,29,42,43), and which probably explains the predictive effect of earlier age at onset on pre-to postoperative memory stability. Preoperatively, the precise pathological status of the hippocampus is unknown, although it can sometimes be inferred from imaging studies (1,44), and from a low ipsilateral memory score or a memory asymmetry during the intracarotid amobarbital test (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this impairment has been identified through an assessment of immediate memory or learning and then delayed memory or retention for the same information following a 20-to 30-min interval. Although a reliable association between visual memory test performance and the right hippocampus has not been found, conventional auditory learning and retention scores in groups of TLE patients have correlated with left hippocampal volume or transverse (T2) relaxation time on magnetic resonance imaging (MRI; Kalviainen et al, 1997;Kilpatrick et al, 1997;Lencz et al, 1992;Loring et al, 1993;Trenerry, Jack, Cascino, Sharbrough, & Ivnik, 1995;Wood, Saling, O'Shea, Berkovic, & Jackson, 2000); metabolic function, as measured by proton magnetic resonance spectroscopy (Kikuchi, Kubota, Hattori, Oya, & Mikuni, 2001;Martin et al, 1999;Sawrie et al, 2000Sawrie et al, , 2001; and hippocampal pathology ratings performed after anterior temporal lobectomy (Baxendale et al, 1998;Rausch & Babb, 1993;Sass et al, 1990).…”
Section: Introductionmentioning
confidence: 99%